A multicountry health partnership programme to establish sustainable trauma training in east, central, and southern African countries using a cascading trauma management course model. (27th April 2015) - Peter, Noel Aaron; Pandit, Hermant; Le, Grace; Nduhiu, Mathenge; Moro, Emmanuel; Lavy, Christopher
Abstract: Background: Injury accounts for 267 000 deaths annually in the nine College of Surgeons of East, Central, and Southern Africa (COSECSA-ASESA) countries, and the introduction of a sustainable standardised trauma training programme across all cadres is essential. We have delivered a primary trauma care (PTC) programme that encompasses both a "provider" and "training the trainers" course using a "cascading training model" across nine COSECSA countries. The first "primary course" in each country is delivered by a team of UK instructors, followed by "cascading courses" to more rural regions led by newly qualified local instructors, with mentorship provided by UK instructors. This study examines the programme's effectiveness in terms of knowledge, clinical confidence, and cost-effectiveness. Methods: We collected pre-training and post-training data from 1030 candidates (119 clinical officers, 540 doctors, 260 nurses, and 111 medical students) trained over 28 courses (nine primary and 19 cascading courses) between Dec 5, 2012, and Dec 19, 2013. Knowledge was assessed with a validated PTC multiple choice questionnaire and clinical confidence ratings of eight trauma scenarios, measured against covariants of sex, age, clinical experience, job roles, country, and health institution's workload. Findings: Post-training, a significant improvement was noted across all cadres in knowledge (19% [95% CI 18·0–19·5]; p<0·05) and clinical confidence (22% [20·3–22·3]; p<0·05). Non-doctors showed a greater improvement in knowledge (22% vs 16%; p<0·05) and confidence (24% vs 20%; p<0·05) than doctors. Candidates attending cascading courses also showed larger improvements in knowledge (21% vs 15%; p<0·002) and clinical confidence (23% vs 19%; p<0·002) than their primary course counterparts. Multivariate regression analysis showed that attending cascading courses (Coef=4·83, p<0·05), being a nurse (Coef=3·89, p=0·007) or a clinical officer (Coef=4·11, p=0·015), and attending a course in Kenya (Coef=9·55, p<0·002) or Tanzania (Coef=9·40, p<0·002) were strong predictors to improvement in multiple choice questionnaire performance. However, improvement in clinical confidence was affected by the job-role of the clinical officer (Coef=6·49, p=0·002) and attending a course in Kenya (Coef=16·12, p<0·02) or Tanzania (Coef=7·01, p<0·05). Cascading courses were on average £2000 less expensive than primary care courses. Interpretation: To the best of our knowledge, this is the largest series in the literature on multicountry trauma management training in sub-Saharan Africa. Our study supports the concept of cascading courses as an educationally and cost-effective method in delivering vital trauma training in low-resource settings led by local clinicians. Funding: Health Partnership Scheme through the UK Department for International Development (DFID).